1993
DOI: 10.1111/j.1365-277x.1993.tb00381.x
|View full text |Cite
|
Sign up to set email alerts
|

Micronutrient intakes in schoolchildren—is supplementation necessary?

Abstract: To compare micronutrient intakes in primary schoolchildren with Dietary Reference Values, dietary intake was investigated in a sample of 136 children from Lothian Region. Most of the children had micronutrient intakes in excess of the reference nutrient intake while the actual percentage of children having intakes below the lower reference nutrient intake was less than predicted. These results suggest that concern regarding the sufficiency of children's diets to provide an adequate intake of micronutrients may… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
1

Year Published

1993
1993
1997
1997

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 3 publications
0
3
1
Order By: Relevance
“…In our sample these children were signi®cantly less likely to get a supplement compared to children whose parents were non-smokers, supplement use decreasing with increasing number of cigarettes smoked. We also found that supplement use decreased with increasing age, older children having been identi®ed as a group that could be at risk of low intakes of some micro-nutrients, possibly as they have greater control over their food choice and intake than younger children (Ruxton et al, 1993).…”
Section: Discussionmentioning
confidence: 64%
See 1 more Smart Citation
“…In our sample these children were signi®cantly less likely to get a supplement compared to children whose parents were non-smokers, supplement use decreasing with increasing number of cigarettes smoked. We also found that supplement use decreased with increasing age, older children having been identi®ed as a group that could be at risk of low intakes of some micro-nutrients, possibly as they have greater control over their food choice and intake than younger children (Ruxton et al, 1993).…”
Section: Discussionmentioning
confidence: 64%
“…It has been suggested that the use of nutritional supplements tends to be indiscriminate and not based on nutrient requirements or matched to needs (Gascon-Barre  et al, 1973). There is some evidence that for children there is no case for the widespread use of supplements (DoH, 1989;Ruxton et al, 1993) and encouraging a varied, balanced diet is regarded as preferable to a less adequate one plus supplements (CPG, 1991). Recent studies suggest that certain groups of children may be at particular risk of consuming a`poorer' quality diet, examples include older girls (Doyle et al, 1994), children from families of lower social class (Adamson et al, 1992) and lower income (Nelson et al, 1993;Doyle et al, 1994).…”
Section: Discussionmentioning
confidence: 99%
“…However, a previous article [15] has suggested that the overall energy and micronutrient intakes of the seven to eight-year-old children in this study compared well with Dietary Reference Values, although non-starch polysaccharide and percentage energy from carbohydrate were too low and percentage energy from fat too high. Thus, the results suggest that nutritional guidelines addressing the energy, vitamin and mineral content of the school meal may be superfluous, although it is acknowledged that the data apply to a specific age group.…”
Section: The Futurecontrasting
confidence: 45%
“…Energy was also lower than the recommendations. However, the overall diets of the children demonstrated energy intakes at or near the Estimated Average Requirement and micro nutrient intakes mainly above the Reference Nutrient Intakes, suggesting that the overall 24 23 26 22 20 18 21 22 19 17 20 23 21 17 35 29 Packed 29 25 30 29 32 25 24 26 22 18 17 24 17 20 35 28 Home 25 26 26 23 24 25 24 22 20 19 15 22 19 17 15 29 NSP = non-starch polysaccharide; Eq = equivalent diets were sufficient [15]. Only iron and NSP intakes were slightly lower than desired and this was reflected in the nutrient profile of the school meals.…”
Section: The Presentmentioning
confidence: 99%